Local anesthetics, procaine, lidocaine, and mepivacaine show vsodilatation but no type 1 allergy: a double-blind, placebo-controlled study - Weinschenk, Stefan; Mergenthaler, Caroline; Strowitzki, Thomas (BioMed research international, 2017)
Background. Therapy with local anesthetics (LAs), also known as neural therapy, is used in integrative medicine because of its anti-inflammatory properties. Ester-linked LAs are often avoided because of their alleged high allergenicity. Little data supports this assumption and hence the importance of our investigation on type-1 allergies against ester- and amide-linked LAs. We performed a prospective, double-blinded, placebo-controlled observational study. Methods. 177 patients received 340 intracutaneous injections with 1% procaine, 0.5% lidocaine, 1% mepivacaine, or saline solution. Every patient received two different tests on each forearm. Reactions were monitored for 15 minutes. Results. No type-1 allergy was observed. The mean erythema diameter of the wheals after 10 minutes was procaine mm, mepivacaine mm, lidocaine mm, and NaCl mm. The wheal diameter of all substances showed a crescendo-decrescendo phenomenon. The procaine and mepivacaine wheals were significantly larger than those of lidocaine and NaCl. No general signs of hypersensitivity were observed. Diameter and intensity were independent of the injection site, order of injection, age, gender, and body mass index. Conclusion. This study shows no higher type-1 allergenicity of the ester-linked LA procaine, compared to the amide-linked LAs lidocaine and mepivacaine, and supports its use in therapy and short-track surgery.
Gesehen am 07.05.2019